The Impact of COVID-19 on Distress Tolerance in Pakistani Men and Women - Shahzad, Salman; Kliewer, Wendy; Bano, Nasreen; Begum, Nasreen; Ali, Zulfiqar (Frontiers in Psychology, 2022)
The Novel Corona Virus (COVID-19) is an infectious disease that spread across the world. Initially, it emerged in the city of Wuhan, China in December 2019. After its emergence, World Health Organization declared it as an outbreak which created global public concerns, later WHO declared it a Pandemic because of its spread across the countries. This pandemic has affected people across the men and women and it brought serious mental health problems. Women in Pakistan are infected with COVID-19 at a much lower rate than men, yet report worse mental health. To explain this paradox, we surveyed 190 Pakistanis (46% male) shortly following the country lockdown, focusing on perceptions of the COVID-19 impact and positive adjustment. Measures used in this study include; Warwick-Edinburgh Mental Well-being Scale (Tennant et al., 2007) and Distress Tolerance Scale (DTS; Simons and Gaher, 2005). Factor analysis revealed five distinct areas related to COVID-19, which did not differ by sex. High endorsement of actions to protect against COVID-19 was related to lower distress tolerance scores, but in different ways for men and women. An in-depth analysis of women’s beliefs and behaviors related to COVID-19 is warranted to understand the Pakistani paradox. Keywords: Sex differences; COVID-19; distress tolerance; well-being; Pakistan